Using machine learning to identify patient characteristics to predict mortality of in-patients with COVID-19 in South Florida - Datta, Debarshi; George Dalmida, Safiya; Martinez, Laurie; Newman, David; Hashemi, Javad; Khoshgoftaar, Taghi M.; Shorten, Connor; Sareli, Candice; Eckardt, Paula (Frontiers in Digital Health, 2023)
The SARS-CoV-2 (COVID-19) pandemic has created substantial health and economic burdens in the US and worldwide. As new variants continuously emerge, predicting critical clinical events in the context of relevant individual risks is a promising option for reducing the overall burden of COVID-19. This study aims to train an AI-driven decision support system that helps build a model to understand the most important features that predict the 'mortality' of patients hospitalized with COVID-19. Methods: We conducted a retrospective analysis of '5,371' patients hospitalized for COVID-19-related symptoms from the South Florida Memorial Health Care System between March 14 th , 2020, and January 16 th , 2021. A data set comprising patients' sociodemographic characteristics, pre-existing health information, and medication was analyzed. We trained Random Forest classifier to predict 'mortality' for patients hospitalized with COVID-19. Results: Based on the interpretability of the model, age emerged as the primary predictor of 'mortality', followed by diarrhea, diabetes, hypertension, BMI, early stages of kidney disease, smoking status, sex, pneumonia, and race in descending order of importance. Notably, individuals aged over 65 years (referred to as 'older adults'), males, Whites, Hispanics, and current smokers were identified as being at higher risk of death. Additionally, BMI, specifically in the overweight and obese categories, significantly predicted 'mortality'. These findings indicated that the model effectively learned from various categories, such as patients' sociodemographic characteristics, pre-hospital comorbidities, and medications, with a predominant focus on characterizing pre-hospital comorbidities. Consequently, the model demonstrated the ability to predict 'mortality' with transparency and reliability. Conclusion: AI can potentially provide healthcare workers with the ability to stratify patients and streamline optimal care solutions when time is of the essence and resources are limited. This work sets the platform for future This is a provisional file, not the final typeset article work that forecasts patient responses to treatments at various levels of disease severity and assesses health disparities and patient conditions that promote improved health care in a broader context. This study contributed to one of the first predictive analyses applying AI/ML techniques to COVID-19 data using a vast sample from South Florida.